DNA methylation regulator-mediated modification patterns and tumor microenvironment characterization in gastric cancer - Qi Meng; Yun-Xin Lu; Dan-Yun Ruan; Kai Yu; Yan-Xing Chen; Min Xiao; Yun Wang; Ze-Xian Liu; Rui-Hua Xu; Huai-Qiang Ju; Miao-Zhen Qiu (Elsevier, 2021)
Growing evidence implies a link between DNA methylation and tumor immunity/immunotherapy. However, the global influence of DNA methylation on the characteristics of the tumor microenvironment and the efficacy of immunotherapy remains to be clarified. In this study, we systematically evaluated the DNA methylation regulator patterns and tumor microenvironment characteristics of 1,619 gastric cancer patients by clustering the gene expression of 20 DNA methylation regulators. Three gastric cancer subtypes that had different DNA methylation modification patterns and distinct tumor microenvironment characteristics were recognized. Then, a DNA methylation score (DMS) was constructed to evaluate DNA methylation modification individually. High DMS was characterized by immune activation status, increased tumor mutation burden, and tumor neoantigens, with a favorable prognosis. Conversely, activation of the stroma and absence of immune cell infiltration were observed in the low DMS group, with relatively poor survival. High DMS was also certified to be correlated with enhanced efficacy of immunotherapy in four immune checkpoint blocking treatment cohorts. In conclusion, the characterization of DNA methylation modification patterns may help to enhance our recognition of the tumor immune microenvironment of gastric cancer and guide more personalized immunotherapy strategies in the future.